Functional Characterisation of Banana (Musa spp.) 2-Oxoglutarate-Dependent Dioxygenases Involved in Flavonoid Biosynthesis - Busche, Mareike; Acatay, Christopher; Martens, Stefan; Weisshaar, Bernd; Stracke, Ralf (Frontiers in Plant Science, 2021)
Bananas (Musa) are non-grass, monocotyledonous, perennial plants that are well-known for their edible fruits. Their cultivation provides food security and employment opportunities in many countries. Banana fruits contain high levels of minerals and phytochemicals, including flavonoids, which are beneficial for human nutrition. To broaden the knowledge on flavonoid biosynthesis in this major crop plant, we aimed to identify and functionally characterise selected structural genes encoding 2-oxoglutarate‐dependent dioxygenases, involved in the formation of the flavonoid aglycon. Musa candidates genes predicted to encode flavanone 3 hydroxylase (F3H), flavonol synthase (FLS) and anthocyanidin synthase (ANS) were assayed. Enzymatic functionalities of the recombinant proteins were confirmed in vivo using bioconversion assays. Moreover, transgenic analyses in corresponding Arabidopsis thaliana mutants showed that MusaF3H, MusaFLS and MusaANS were able to complement the respective loss-of-function phenotypes, thus verifying functionality of the enzymes in planta. Knowledge gained from this work provides a new aspect for further research towards genetic engineering of flavonoid biosynthesis in banana fruits to increase their antioxidant activity and nutritional value.